Hibiscus sabdariffa Linn. (Roselle) protects against nicotine-induced heart damage in rats - Satirah Zainalabidin,; Siti Nor Farhanah Sh Nor Shahidin,; Siti Balkis Budin, (Universiti Kebangsaan Malaysia, 2016)
Nicotine has been identified as one of the causal factor for oxidative stress, hypertension and hyperlipidemia. Roselle has been widely studied for its potential as an antioxidant, antihyperlipidemic and antihypertensive. However, no studies have been done to investigate if roselle could diminish the oxidative stress caused by nicotine which could further lead to cardiac damages. Thus, this study was aimed to investigate the effect of roselle extract (HSE) on blood pressure, serum lipid profile, oxidative stress marker levels and histological changes to the heart in nicotine-treated rats. A total of 21 Sprague-Dawley rats were randomly divided into 3 groups (n=7 per group): Control group received normal saline (0.5 mL/day, i.p); nicotine group received 0.6 mg/kg/BW nicotine (i.p); and treated group received 100 mg/kg/b.w HSE through oral force feeding followed with 0.6 mg/kg/b.w nicotine (i.p) for 21 consecutive days. The results showed that HSE significantly (p>0.05) reduced the heart rate but no effect to the blood pressure. For lipid profile study, HSE increased the high-density lipoprotein (HDL) concentration significantly (p<0.05) in rats given with nicotine, without any significant changes in total cholesterol, triglyceride and low-density ipoprotein (LDL) concentration. Besides, HSE treatment was also found to reverse malondialdehyde (MDA) level, superoxide dimustase (SOD) enzyme activity and protein concentration significantly (p<0.05) in nicotine-treated rats. In summary, these results indicated that HSE is an effective antioxidant against oxidative damage in heart caused by nicotine, but not as antihyperlipidemic and antihypertensive agent in this rat model.